ENGLISH TEACHERS' IDENTITY INFLUENCE ON EMOTIONS AND BELIEFS: A NARRATIVE INQUIRY INTO PRIVATE AND STATE SCHOOL TEACHERS - Intan Clara Briliant Mallisa; Concilianus Laos Mbato (Magister Scientiae, 2023)
Teacher identity, emotions, and beliefs are all interconnected aspects of a teacher's professional self-concept and are essential to effective teaching. Therefore, this study aims to find and prove that teacher identity is very influential with emotions and beliefs. The writer used qualitative research from the life experiences of two junior high school English teachers from private and public schools in Tarakan, Nort Kalimantan. This research used a narrative inquiry method with in-depth interviews. An in-depth interview was the primary data, and the support data were collected from some journals and online resources relevant to this study. Furthermore, the results of the interview showed that both teachers had strengths and weaknesses in forming their teachers' identities, emotions, and beliefs.  However, the best and most prominent is the teacher's answer from the private school.